Coming of age : speeches by Prime Minister of St. Kitts & Nevis - the first two terms, July 1995 to October 2004; edited and introduced by Kenneth G. Tilley - Douglas, Denzil L. (Ian Randle Publishers KingstonJM, 2009)
Presents the speeches on the policies and programmes of the St. Kitts & Nevis government as they evolved under the Denzil Douglas' administration during his first two terms in office.